Education Supervision in Increasing Competence Teachers in Curriculum 2013 (Study of Education Management Analysis) - Bahdin Nur Tanjung (Britain International for Academic Research (BIAR) Publisher, 2020)
Administrators must be transferred to ensure quality learning. That is, that the success of the implementation of supervision is measured by increasing student learning achievement. Tenriningsih (2009) believes that there is a positive and significant direct relationship between master's performance and positive and significant achievement between student achievements through teaching administrators